PENGARUH LITERASI KEUANGAN DAN PENDAPATAN TERHADAP MINAT INVESTASI MAHASISWA DIERA DIGITAL - Lestari, Nastiti Dwi; Listiawati, Aliza (Perwira Journal of Economics & Business, 2025)
This research is a quantitative study motivated by the large number of students who do not yet understand the correct investment concepts, due to low financial literacy levels and unstable incomes. This study aims to analyze the influence of financial literacy and income on the investment interest of students at Perwira Purbalingga University. All active students of Perwira Purbalingga University constitute the population, from which a sample of 50 respondents was taken using purposive sampling technique. In conducting data analysis, multiple linear regression analysis was used on the IBM SPSS 27 software, sourced from primary data in the form of a Likert scale questionnaire. The results show that financial literacy and income have a positive and significant impact on investment interest. These findings indicate that an increase in financial literacy can enhance students' interest in investing, while higher income provides flexibility in financial management and participation in investments. .